Primary aldosteronism and aldosterone-associated hypertension. Issue 7 (27th June 2008) - Rayner, B
Abstract : The field of primary aldosteronism (PA) and aldosterone-related hypertension has undergone rapid evolution. From a relatively rare curiosity PA has become a common problem particularly in selected hypertensive populations. Patients with PA and aldosterone-related hypertension appear to be at higher cardiovascular and renal risk than comparable patients with essential hypertension probably due to the pleiotropic effects of aldosterone. Aldosterone is also linked to metabolic syndrome and diabetes. The aldosterone-to-renin ratio (ARR) has allowed the widespread screening for PA, but the exact cut-off values may vary in different population groups. All patients with hypertension and hypokalaemia, and young patients with hypertension, hypertension with an incidental adrenal mass, and severe or resistant hypertension should be screened. The use of the ARR to screen all hypertensives for PA is controversial as the test lacks specificity and many patients with false-positive tests will undergo complex and expensive testing to confirm the diagnosis. The fludrocortisone suppression test, the saline infusion test or 24-hour aldosterone excretion may be used to confirm PA in patients with a positive ARR. Adrenal venous sampling is the most reliable test to detect the presence of an aldosterone-producing adenoma, but spiral CT scan or adrenocortical scintigraphy may be useful in centres without facilities for adrenal venous sampling. Spironolactone is emerging as an important antihypertensive agent in patients with resistant hypertension and aldosterone-related hypertension. The ARR may be a useful guide to drug selection in hypertensives patients, but further research is needed to make more definitive recommendations.